PERENCANAAN JEMBATAN CABLE STAYED 200 METER (Studi Kasus : Jembatan Cijambe Garut) - Syapril Janizar; Habdullah Habdullah; Felix Setiawan; Lucky Ampearawan Schipper (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2022)
In this final project, we discuss the Planning of a Cable Stayed Bridge with a Length of 200 meters. This bridge has a length of 200 meters with a span of 180 meters and an edge span of 20 meters. The bridge cable configuration uses a semi harp pattern with a two planes system cable position. The bridge has a vehicle floor width of 6.00 meters, and a sidewalk of 1.5 meters right and left. As for the results of this design, the secondary structure of the bridge consists of railings with a hollow steel profile with a diameter of 60.5, curbs with a thickness of 250 mm, a vehicle floor plate with a thickness of 200 mm concrete slab and 50 mm asphalt, and a girder consisting of a WF 1300,550 transverse girder. 28.34, longitudinal girder WF 600.200.11.17, and cantilever girder WF 300.150.6.5.9 for the connection of the girder itself using a simple connection with an L elbow plate. While the main structure consists of the main girder using rectangular twin box girders with dimensions of 2500.1500.50.50, then stay cable is made up of 7 – wire strands with a diameter of 15.2 mm and a pylon which is designed using reinforced concrete material with dimensions of 4000 mm x 3000 mm with a cavity inside.